All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 36538 by tanmay.chaudhury50@gmail.com last updated on 03/Jun/18
∫dx(a+bx2)b−ax2
Commented by abdo.msup.com last updated on 03/Jun/18
wehaveb−ax2=b(1−(abx)2ifab>0changementabx=sin(t)giveabx=sin2t⇒x=basin2t⇒I=∫1(a+bb2a2sin4t)b.abcost2basintcostdt=2ba∫sinta(a3+b3sin4t)a2dt=2ba∫sinta3+b3sin4tdt...becontinued...
Terms of Service
Privacy Policy
Contact: info@tinkutara.com